The influence of socio-economic variables on the prevalence of periodontal disease in South Africa - Gugushe, T S (SADJ (Houghton), 1998)
The purpose of this study was to assess the influence of race, level of education and income on the frequency distribution of periodontal disease in an adult South African population. A retrospective data analysis of the National Oral Health Survey (NOHS, 1988/89) was done on 3,763 adults with an age range of 20-64 years. From the results obtained it would appear that socio-economic variables have an influence on the prevalence of periodontal disease in South Africa.